The Climate of the Mediterranean Region : From the past to the future. - Lionello, P. (Elsevier Science, 2012)
The Mediterranean region contains a diverse and interesting climate ranging from areas with permanent glaciers to areas of subtropical, semiarid regions. The region is potentially sensitive to climate change and its progress has environmental, social, and economic implications within and beyond the region. Produced by the Mediterranean Climate Variability and Predictability Research Networking Project, this book reviews the evolution of the Mediterranean climate over the past two millennia with projections further into the twenty-first century as well as examining in detail various aspects of.